Do 'Flexible' Exchange Rates of Developing Countries Behave Like the Floating Exchange Rates of Industrialized Countries? - Wickham, Peter (IMF Working Papers; Working Paper ;, 2002)
The paper examines the behavior of daily spot exchange rates for a sample of industrialized countries which are generally considered to be floating with only occasional official foreign exchange market intervention. This behavior is then compared to the behavior of the exchange rates of a sample of sixteen developing countries whose regimes are often classified as being 'flexible'. Considerable differences in the way these developing countries' exchange rate regimes operate is apparent from the daily data, with some sharing similarities with the regimes of the industrialized countries and with others demonstrating regime shifts and other marked discontinuities.